SEFALGIA PADA PENDERITA OBSTRUCTIVE SLEEP APNEA DI LABORATORIUM TIDUR RS MITRA KEMAYORAN JAKARTA - Andreas Prasadja*, Maula Gaharu** (Neurona Majalah Kedokteran Neuro Sains, 2009)
BACKGROUND CEPHALGIA AND SLEEP DISORDERS HAS CLOSE RELATION BOTH HENCE OBSTRUCTIVE SLEEP APNEA OSA AS ONE OF SLEEP DISORDER FREQUENTLY CAUSES CEPHALGIA THAN OTHER SLEEP DISORDERS